OPTIMIZATION OF DEMAND FOR LEADING SMI PRODUCTS IN PACITAN DISTRICT - Kunto Inggit Gunawan; Mataji Mataji (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Empowerment of Micro, Small and Medium Enterprises as defined in Republic Act No. 20 Year 2008 About the Micro, Small and Medium Enterprises need to be conducted in a thorough, optimal, and sustainable through the development of a climate that is conducive, giving the opportunity seeks, support, protection, and development business as wide as possible, so as to be able to improve the position, role, and potential of the business Micro, Small and Medium Enterprises in realizing economic growth ,equity and increasing people's income , creating job opportunities , and alleviating poverty. The principle of empowering Micro, Small, and Medium Enterprises as mandated by Law of the Republic of Indonesia No. 20 of 2008 is: a. Growing independence, togetherness, and entrepreneurship for Micro, Small and Medium Enterprises to work on their own initiative; b. The realization of transparent, accountable and fair public policies ; c. Regional potential -based and market- oriented business development in accordance with the competencies of Micro, Small, and Medium Enterprises; d. Increased power competitiveness Enterprises Micro, Small, and Medium Enterprises; and e. Implementation of planning, implementation, and control in an integrated manner. The crucial issue is that not only SMEs in Pacitan Regency are able to produce superior products, but what is more important is how superior products can be marketed effectively and efficiently so that on a macro level it encourages regional economic growth and on a micro scale it encourages an increase in the income of IKM business actors. On this basis, a rational study based on existing regulations is needed to determine a marketing strategy fordeveloping superior products in the Pacitan Regency area . Based on the identification of strengths, weaknesses, opportunities and threats, it shows that: strengths and opportunities have a larger portion when compared to threats and weaknesses, even though weaknesses and threats have a smaller portion but should not be ignored, so the Department of Trade and Industry must be able to optimize development superior products as a support for income in order to improve the welfare of the community.